2023
DOI: 10.3390/photonics10050509
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Emitting Lasers with Surface Metastructures

Abstract: Vertical-cavity surface-emitting lasers (VCSELs) have been widely used in consumer electronics, light detection and ranging, optical interconnects, atomic sensors, and so on. In this paper, a VCSEL with the surface metastructure like one-dimensional high-contrast grating (HCG), based on the HCG-DBR vertical cavity, was first designed and fabricated. The polarization characteristic of the HCG-VCSEL were experimentally studied. The p-doped top 4-pair DBR for the current spreading and the direction shift between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Recently, HCG VCSELs have shown significant potential in terms of further suppressing relative-intensity noise (RIN) and benefiting the high-speed transmission of VCSELs. Here, Prof. Anjin Liu et al demonstrated that surface-emitting lasers with surface metastructures could attain this goal [5].…”
mentioning
confidence: 99%
“…Recently, HCG VCSELs have shown significant potential in terms of further suppressing relative-intensity noise (RIN) and benefiting the high-speed transmission of VCSELs. Here, Prof. Anjin Liu et al demonstrated that surface-emitting lasers with surface metastructures could attain this goal [5].…”
mentioning
confidence: 99%